Solubility and Phytoavailability of Phosphorus and Lead in a Contaminated Soil Amended with Two Phosphorus Fertilizers. Issue 17 (24th September 2016) - Badrloo, Toraj Afshari; Nobariyan, Mohammad Reza Shoaibi; Bostani, AbdolAmir; Ghorbani, Hadi; Abbaspour, Ali
ABSTRACT: Application of some chemical amendments such as diammonium phosphate (DP) and triple superphosphate (TP) to contaminated soils is an effective technique to stabilize Pb and decrease its uptake by plants. A calcareous soil was spiked with the rates of 0, 250, 500, and 750 mg of lead (Pb) kg −1 soil as Pb acetate, treated with 760 mg of P kg −1 soil as DP and TP, and incubated for 120 days. The results showed that available phosphorus (P) increased immediately after addition of DP or TP to soil, but it declined sharply after only a few days of incubation time. Pot experiment was conducted on sorghum and spinach. The accumulation of Pb was significantly ( P ≤ 0.05) lower in sorghum than in spinach, and also was lower in soil amended with DP than TP. The decreased Pb accumulation in the plants by application of both amendments was mainly attributed to the formation of chloropyromorphite.